2021
DOI: 10.1177/21501327211023871
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Primary Care Contributions to Behavioral Health: A Cross-sectional Study Using Medical Expenditure Panel Survey

Abstract: Objectives To assess primary care contributions to behavioral health in addressing unmet mental healthcare needs due to the COVID-19 pandemic. Methods Secondary data analysis of 2016 to 2018 Medical Expenditure Panel Survey of non-institutionalized US adults. We performed bivariate analysis to estimate the number and percentage of office-based visits and prescription medications for depression and anxiety disorders, any mental illness (AMI), and severe mental illness (AMI) by physician specialty (primary care,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
0
14
0
2
Order By: Relevance
“…We also found that while the number of visits for depression was similar in the return period compared to the pre-period, the number of visits for anxiety was higher. Understanding the changes in visits for depression and anxiety in primary care is particularly important as most patients with a mental illness consult a primary care physician [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also found that while the number of visits for depression was similar in the return period compared to the pre-period, the number of visits for anxiety was higher. Understanding the changes in visits for depression and anxiety in primary care is particularly important as most patients with a mental illness consult a primary care physician [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…More specific contributions of primary care in addressing mental health needs were studied in a recent article published in the Journal of Primary Care & Community Health (Jetty et al, 2021). Data from 2016–2018 revealed that, on average, 40% of all acute mental illness visits were completed by a PCP in the primary care setting.…”
mentioning
confidence: 99%
“…This is in line with prior literature by Xierali et al (2013), which indicates that PCPs serve as the primary managers of psychiatric illness in roughly one third of their patients and that two thirds of patients with depression receive treatment for their depressions from PCPs. Given a large percentage of mental health needs are identified and managed by PCPs, it is problematic that they were not considered in the AAMC’s workforce modeling (Donaldson et al, 1996; Jetty et al, 2021; Xierali et al, 2013). As evidenced above, any workforce increases to meet unmet mental health needs would undoubtedly lead to an increased demand for PCPs as well.…”
mentioning
confidence: 99%
“…(1) Primary care clinicians already identify and treat mild to moderate behavioral health conditions, particularly depression and anxiety disorders (Jetty et al, 2021; University of Michigan Behavioral Health Workforce Research Center, 2019). The treatment primary care practices can provide is greatly expanded in scope by integrated behavioral health.…”
mentioning
confidence: 99%
“…To advocate to move these recommendations forward, we must be clear first on what we mean by integrated behavioral health in primary care and then address misperceptions. Primary care clinicians already identify and treat mild to moderate behavioral health conditions, particularly depression and anxiety disorders (Jetty et al, 2021; University of Michigan Behavioral Health Workforce Research Center, 2019). The treatment primary care practices can provide is greatly expanded in scope by integrated behavioral health.…”
mentioning
confidence: 99%